Is the Cyber Security Awareness Perspective Different? - Sulkhanul Umam (Profesional Muda Cendekia Publishing, 2020)
Everybody needs internet, so does SMEs, but the internet likes a knife. If wrong, can be injure users. so users must care about security in using the internet. This is called the cybersecurity awareness. a person's actions are influenced by perceptions and perceptions appear to be motivated by an ethical orientation. so it is important to examine whether there are differences in cybersecurity awareness that are motivated by ethical orientations. This study conducted in Bantul, Yogyakarta with study subjects were 59 SMEs. The test results to see differences in awareness using the Mann Whitney test show that there is no difference regarding cyber security awareness, both in individuals with an ethical orientation of idealism and relativism. Cyber ​​security awareness is absolutely necessary so that users avoid every crime that exists.